Por um currículo alternativo: educação para as relações étnico-raciais em um pré-universitário popular - Squio, Luigi Bertoldo (2024)
The following research seeks to understand how the faculty of the Popular Pre-University Alternativa builds its curriculum in relation to Education for Ethnic-Racial Relations. The intention is to use the qualitative method, through the Investigative-Formative Dialogical Circles, developed by the DIALOGUS group, based on a reinvention of Freirean Culture Circles (HENZ, C. I.; FREITAS, L. M.; SILVEIRA, M. N., 2018), in dialogue with Gadamer's Philosophical Hermeneutics (1997), Josso's research-training (2007) and with characteristics of action research (COSTA, 1994; THIOLLENT, 1999). Five Circles were held with the P.U.P Alternativa faculty during the 2024 school year. As a theoretical framework, we used the works of Freire (1987, 2001, 2004), Brandão (1999, 2006, 2009) and Wanderley (2010), which contribute to a definition of Popular Education; Sacristán (1998, 2013), Arroyo (2013, 2015) and Apple (1982, 1989, 1996), for the conceptualization of the curriculum. The issue of Education for Ethnic-Racial Relations was addressed through the concepts of race, racism, blackness, and whiteness with Fields (1982), Almeida (2019), Fanon (2008, 1980), Munanga (2000, 2009), hooks (2013, 2019), Bento (2022), and Cardoso (2014). We believe that the implementation of the Investigative-self(trans)formative Dialogical Circles promoted significant dialogues with the program's faculty, around how we work on Education for Ethnic-Racial Relations. By identifying racism and whiteness as barriers to the development of Popular Education, we conclude that we must mobilize ongoing training processes that aim at coherence and humility as essential postures in the fight for a humanizing pedagogy, inspired by Paulo Freire. Furthermore, we propose a curricular reorganization based on dialogue, the construction of value-based narratives about the black population and the deconstruction of whiteness, in favor of an anti-racist Popular Education, creating a welcoming space for black students and educators, enabling their entry into higher education.